Recurrent supramolecular scenarios within complex 3-D hydrogen bond networks derived from organic ammonium salts of (4-amino-1-hydroxybutylidine)-1, 1-bisphosphonic acid. Issue 37 (11th September 2017) - Deacon, G. B.; Forsyth, C. M.; Greenhill, N. B.; Junk, P. C.
Abstract : Reactions of (4-amino-1-hydroxybutylidine)-1, 1-bisphosphonic acid (LH5 ) with organic amines or diamines in aqueous solution yields crystalline compounds of the general formula [(RN)H]2 [LH3 ] or [(R'N)H2 ][LH3 ]. Abstract : Reactions of (4-amino-1-hydroxybutylidine)-1, 1-bisphosphonic acid (alendronic acid = LH5 ) with organic amines or diamines in a 1 : 2 or 1 : 1 ratio in aqueous solution gave a range of nine new compounds of the general formula [(RN)H]2 [LH3 ] or [(R′N)H2 ][LH3 ]. Crystal structures are reported for: (i) [enH2 ][LH3 ]·2(H2 O)1 ; (ii) [MeenH2 ][LH3 ]·3(H2 O)2 ; (iii) [Me2 enH2 ][LH3 ]·3.5(H2 O)3 ; (iv) [Et2 enH2 ][LH3 ]·2(H2 O)4 ; (v) [cdaH2 ][LH3 ]·3(H2 O)5 ; (vi) [xdaH2 ][LH3 ]·4(H2 O)6 ; (vii) [odaH2 ][LH3 ]·2(H2 O)·0.5(EtOH)7 ; (viii) [PheaH]2 [LH3 ]·2(H2 O)8 ; (ix) [melH]2 [LH3 ]·7(H2 O)9 (en = H2 N(CH2 )2 NH2 ; Meen = Me(H)N(CH2 )2 NH2 ; Me2 en = Me(H)N(CH2 )2 N(H)Me; Et2 en = Et2 N(CH2 )2 NH2 ; cda = trans-rac -1, 2-C6 H10 (NH2 )2 ; xda = m -C6 H4 (NH2 )2 ; oda = H2 N(CH2 )8 NH2 ; Phea = 2-Ph(CH2 )2 NH2 ; mel = 1, 3, 5-C3 N3 (NH2 )3 ). Each structure displays numerous hydrogen bond interactions between bisphosphonate anions, the (alkyl)ammonium cations and water molecules resulting in 3-D network materials. Compounds1, 7 and8 display identical 2-D sheets composed of [LH3 ] 2− anions and water molecules approximately 12 Å thick and pillared by the [enH2 ] 2+ or [onH2 ] 2+ cations or a double layer of [PheaH] + cations. A similar pillared structure is also observed in compound9 where the 2-D anion layers are separated by regions of hydrogen bonded and π-stacked [melH] + cations. The anion layer, although similar to that of compounds1, 7 or8, contains a significantly higher proportion of water molecules. The substituted ethylene diamine derivatives2, 3, and4 also display a consistent (but not identical) set of flat 2-D sheets of [LH3 ] 2− anions and water molecules, with the organic diammonium cations and further water molecules sandwiched in between. In contrast to the above lamella type structures, the cda and xda derivatives, 5 and6, comprise tessellated columns of anion and cations. A consistent feature of all the above structures is the head-to-tail arrangement of [LH3 ] 2− anions held by strong, charge assisted, N(H)⋯O hydrogen bonds.